Coprophagy in nineteenth-century psychiatry. (29th March 2019) - Moore, Alison M.
ABSTRACT: This paper shows how Austrian psychiatrists of the 1870s developed the first pathological accounts of institutional coprophagia, examining how they related the behaviour to mental illness and dementia. These ideas about coprophagia contrasted dramatically to the long European pharmacological tradition of using excrement for the treatment of a wide range of health conditions. Recent medical scholarship on institutional coprophagia is also reviewed here, with a novel hypothesis proposed about why some patients in long-term care resort to the behaviour in institutions where there is little opportunity for healthy human–microbe interactions.